2019
DOI: 10.1186/s13005-019-0206-8
|View full text |Cite
|
Sign up to set email alerts
|

HF etching of CAD/CAM materials: influence of HF concentration and etching time on shear bond strength

Abstract: Background The required pretreatment of CAD/CAM ceramic materials before resin composite cement application varies among studies. The aim of the present study was to evaluate the effect of hydrofluoric acid concentration and etching time on the shear bond strength (SBS) of two adhesive and two self-adhesive resin composite cements to different CAD/CAM ceramic materials. Methods SBS of two adhesive (Panavia V5, Kuraray, [PV5]; Vita Adiva F-Cem, Vita Zahnfabrik, [VAF]) an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
25
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 51 publications
2
25
0
3
Order By: Relevance
“…A hybrid ceramic, a member of this new class, contains 86% ceramic and 14% acrylate polymer network [urethane dimethacrylate (UDMA) and triethylene glycol dimethacrylate (TEGDMA)] in weight (2,16,17). This material has been recognized to have better machinability and fracture toughness, enhanced flexibility, and decreased brittleness, hardness, and rigidity compared to ceramics (13,18,19).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A hybrid ceramic, a member of this new class, contains 86% ceramic and 14% acrylate polymer network [urethane dimethacrylate (UDMA) and triethylene glycol dimethacrylate (TEGDMA)] in weight (2,16,17). This material has been recognized to have better machinability and fracture toughness, enhanced flexibility, and decreased brittleness, hardness, and rigidity compared to ceramics (13,18,19).…”
mentioning
confidence: 99%
“…HF selectively removes the glassy phase and exposes the crystalline structure (5), while silane promotes adhesion (24) by a reaction between the organofunctional groups of silane and the functional groups of the resin cement (25). However, there are disputes concerning the concentration and duration of HF (18). It has been reported that depending on the concentration and duration of HF, mechanical resistance of ceramics may decrease (26).…”
mentioning
confidence: 99%
“…Assim, a partir desses estudos, verificamos que a maioria dos artigos demonstram impactos negativos nos tempos prolongados de aplicação do HF, uma vez que tempos superiores a 60s podem enfraquecer a estrutura da cerâmica. A literatura ainda traz outros estudos que confirmam esses achados, abordando 60s para o condicionamento desse tipo de cerâmica, por garantir dissolução suficiente da matriz vítrea, proporcionando adequada força de união (Moura et al, 2020;Straface et al, 2019).…”
Section: Discussionunclassified
“…Esse condicionamento é capaz de produzir porosidades superficiais e aumentar a energia de superfície, promovendo retenção micromecânica com o agente cimentante (França et al, 2020). Apesar do papel do HF ser indiscutível na adesão protética, ainda existem controvérsias quanto à concentração e seu tempo de aplicação (Straface et al, 2019), que variam de acordo com cada tipo cerâmico (Mokhtarpour et al, 2017;Veríssimo et al, 2019).…”
Section: Introductionunclassified
“…For IPS Emax: The intaglio of each restoration was etched with DentoBond Porcelain Etch (hydrofluoric acid 8%) for 20 seconds (11) , then rinsed with water and dried with moisture-free oil-free air until a frosted white appearance was evident. Then, the DentoBond Porcelain Silane (DentoBond Porcelain Etch, ITENA, France) was brushed on the etched ceramic surface and left for 1 minute, then dried well with moisture free oil-free compressed air according to the manufacturer's instructions.…”
Section: Surface Treatment Of the Restorationsmentioning
confidence: 99%